Gas phase permeation in-situ synthesis method of hybrid photoresist
By vapor-phase penetration of metal oxides on the photoresist pattern, metal nanoparticles are generated, which solves the problem of collapse and insufficient exposure of photoresist during the etching process, and achieves high etching resistance and good pattern transfer ability.
Patent Information
- Application Number
- CN202510248177.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-04
- Publication Date
- 2025-04-15
AI Technical Summary
Existing photoresist is prone to collapse during the etching process, and the addition of metal oxide materials can improve the etching resistance, but it will lead to insufficient exposure.
By vapor-phase penetration of metal oxides on the photoresist pattern after exposure and development, metal nanoparticles are generated, thereby enhancing the etching resistance of the photoresist while avoiding dopants affecting the exposure process.
It is achieved that when the photoresist thickness is small, good pattern transfer ability is maintained, and the problem of insufficient exposure is avoided, which enhances the etching resistance of the photoresist.
Smart Images

Figure CN119828416A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photoresist materials, and particularly relates to a vapor phase infiltration in-situ synthesis method of hybrid photoresist. Background Art
[0002] Photolithography is a critical step in semiconductor manufacturing. The main processes include: 1. Gluing: evenly apply photoresist on the surface of the silicon wafer. 2. Pre-baking: heat the silicon wafer after glue coating to remove residual solvents in the photoresist and improve its photosensitivity and adhesion. 3. Alignment: use a photolithography machine to accurately align the pattern on the mask to the specified position on the silicon wafer to ensure the accuracy of the pattern in subsequent steps. 4. Exposure: irradiate ultraviolet light (UV) or electron beam (E-beam) onto the photoresist through the mask, causing a photochemical reaction in the irradiated photoresist area. 5. Development: use a developer to develop the exposed photoresist, so that the photoresist in the exposed or unexposed areas (depending on the type of photoresist) is dissolved and removed, forming a photoresist structure corresponding to the mask pattern. Subsequent steps include etching and removing the photoresist, specifically: using the photoresist pattern as an etching mask to etch the exposed area of the silicon wafer or substrate to form the desired microstructure. After the etching is completed, the photoresist is removed using a wet chemical solvent or dry plasma to expose the etched substrate pattern.
[0003] In advanced processes, when the critical size of the device is much smaller than the thickness of the photoresist, the photoresist pattern will collapse during the etching process, but reducing the thickness of the photoresist will lead to a worse pattern transfer effect in the etching process. Therefore, it is necessary to use a photoresist with both high etching resistance and high mechanical properties to achieve the goal of having good pattern transfer ability even when the photoresist thickness is small.
[0004] By adding metal oxide materials to photoresists, the etching resistance of composite photoresists can be effectively improved, thereby improving the pattern transfer ability of hybrid photoresists. However, the introduction of metal atoms will increase the initial exposure dose of photoresists, resulting in insufficient exposure. Therefore, a method is needed to enhance the etching resistance of photoresists without affecting other process steps.
[0005] The vapor phase infiltration method is a simple method for preparing organic-inorganic hybrid materials, which can quickly dope inorganic components in the bulk phase of polymer materials without being limited by the shape and structure of the polymer materials. Utilizing this technical feature, the present invention can perform vapor phase infiltration of metal oxides on a substrate covered with a photoresist pattern after exposure and development, thereby achieving the purpose of enhancing the etching resistance of the photoresist material while avoiding the influence of dopants on the exposure process. Summary of the invention
[0006] In view of the above-mentioned shortcomings of the prior art, the purpose of the present invention is to provide a hybrid photoresist vapor infiltration in-situ synthesis method, which is used to solve the problems of poor mechanical properties and etching resistance of the photoresist in the prior art, and the collapse of the photoresist pattern during the transfer of high aspect ratio patterns. Although the addition of metal oxide materials can improve the etching resistance of the photoresist, it will also increase the initial exposure dose of the photoresist material, thereby affecting the exposure effect and other problems.
[0007] To achieve the above objectives and other related objectives, the present invention is achieved through the following technical solutions.
[0008] The first aspect of the present invention provides a method for in-situ synthesis of a hybrid photoresist by vapor infiltration, comprising the following steps:
[0009] The silicon substrate loaded with photoresist is placed in a deposition device for preheating, and then a metal precursor, an inert gas, deionized water and an inert gas are introduced in sequence for gas phase infiltration circulation to generate metal nanoparticles inside the photoresist to obtain a hybrid photoresist.
[0010] In some embodiments of the present invention, the photoresist is composed of a photosensitive resin, a photosensitizer, an organic solvent and an additive.
[0011] In some embodiments of the present invention, the silicon substrate loaded with photoresist is subjected to ultraviolet exposure and development to obtain a silicon substrate with patterned photoresist.
[0012] In some embodiments of the present invention, the thickness of the photoresist loaded on the silicon substrate is 200-400 nm.
[0013] In some embodiments of the present invention, the preheating temperature is 90-120° C.; the preheating time is 25-35 min.
[0014] In some embodiments of the present invention, the metal precursor is trimethylaluminum or diethylzinc.
[0015] In some embodiments of the present invention, the inert gas is argon.
[0016] In some embodiments of the present invention, the number of cycles of the vapor infiltration is 1-7; each cycle includes sequentially introducing a metal precursor, an inert gas, deionized water, and an inert gas.
[0017] In some embodiments of the present invention, the molar ratio of the metal precursor to the deionized water introduced in each gas phase infiltration cycle is 1:(1-2).
[0018] In some embodiments of the present invention, the metal nanoparticles are aluminum oxide or zinc oxide.
[0019] In some embodiments of the present invention, the mass fraction of the metal nanoparticles generated inside the photoresist is 2-10wt%.
[0020] The second aspect of the present invention provides a hybrid photoresist prepared by the above synthesis method.
[0021] The present invention also provides the use of the hybrid photoresist prepared by the above synthesis method in etching.
[0022] The present invention also provides an etching method, which comprises the following steps: etching a silicon substrate loaded with a hybrid photoresist once, transferring the pattern to the silicon substrate, and then removing the hybrid photoresist remaining on the surface of the silicon substrate by a secondary etching. The hybrid photoresist is a hybrid photoresist obtained by the above-mentioned synthesis method.
[0023] In some embodiments of the present invention, the primary etching and / or secondary etching is performed in a reactive ion etching device.
[0024] In some embodiments of the present invention, the etching gas used in the primary etching is a mixture of sulfur hexafluoride and oxygen.
[0025] In some embodiments of the present invention, the etching time is 20-40s.
[0026] In some embodiments of the present invention, the etching gas for the secondary etching is oxygen.
[0027] In some embodiments of the present invention, the secondary etching time is 4-6 minutes.
[0028] In some embodiments of the present invention, the flow ratio of sulfur hexafluoride to oxygen is (9-11):1.
[0029] As described above, the vapor infiltration in-situ synthesis method of a hybrid photoresist of the present invention has the following beneficial effects:
[0030] (1) Performing an in-situ vapor infiltration of a metal oxide on a silicon substrate with a patterned photoresist after exposure and development can prevent the doping component from absorbing photons during the exposure process, further preventing insufficient exposure of the photoresist.
[0031] (2) The in-situ vapor infiltration method of the present invention will not destroy the shape and structure of the existing patterned photoresist, and can also enhance the etching resistance of the pattern sidewall.
[0032] (3) The hybrid photoresist prepared by the present invention can be completely removed by oxygen plasma etching, so that the doped components only participate in the etching step without affecting the rest of the process. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 It is a schematic diagram of the photolithography process, wherein line 1 is a schematic diagram of pure photoresist etching of comparative example 3, and line 2 is a schematic diagram of vapor infiltration in-situ synthesis of hybrid photoresist and hybrid photoresist etching of Example 1 of the present invention.
[0034] Figure 2 Shown is the infrared spectrum of the hybrid photoresist (doped aluminum oxide) of Example 1 of the present invention.
[0035] Figure 3 The etching rates of the hybrid photoresist (doped with aluminum oxide) of Example 2 and the hybrid photoresist (doped with zinc oxide) of Example 3 of the present invention after different cycles of vapor infiltration treatment are shown.
[0036] Figure 4 It shows the etching rate of the silicon substrate deposited with a metal oxide (aluminum oxide) film in comparative example 1 of the present invention and the silicon substrate deposited with a metal oxide (zinc oxide) film in comparative example 2 after different cycles of vapor infiltration treatment.
[0037] Figure 5 It shows the etching selectivity ratio obtained by the etching rate of comparative example 1 / the etching rate of embodiment 2 and the etching selectivity ratio obtained by the etching rate of comparative example 2 / the etching rate of embodiment 3 under different numbers of gas phase infiltration treatments of the present invention. DETAILED DESCRIPTION
[0038] Hereinafter, an embodiment of the specifically disclosed vapor phase infiltration in-situ synthesis method of hybrid photoresist will be described in detail.
[0039] In order to solve the problems that the mechanical properties and etching resistance of photoresists in the prior art are poor, the photoresist pattern collapses during the transfer of high aspect ratio patterns; although adding metal oxide materials can improve the etching resistance of photoresists, it will also increase the initial exposure dose of photoresists, thereby affecting the exposure effect. The present invention achieves the enhancement of the etching resistance of photoresists by performing vapor phase infiltration of metal oxides on a silicon substrate with patterned photoresists after exposure and development, while avoiding the influence of dopants on the exposure process. On this basis, the present invention is completed.
[0040] [Vapor infiltration in-situ synthesis method of hybrid photoresist]
[0041] The first aspect of the present invention provides a method for in-situ synthesis of a hybrid photoresist by vapor infiltration, comprising the following steps:
[0042] The silicon substrate loaded with photoresist is placed in a deposition device for preheating, and then a metal precursor, an inert gas, deionized water and an inert gas are introduced in sequence for gas phase infiltration circulation, so that metal nanoparticles are generated inside the photoresist to obtain a hybrid photoresist. Specifically: the silicon substrate loaded with photoresist is placed in a cavity of a deposition device for preheating, and a gas phase infiltration circulation is performed after the preheating is completed. The gas phase infiltration circulation is firstly introduced into a metal precursor, so that the silicon substrate loaded with photoresist is immersed in the metal precursor atmosphere for infiltration, so that the metal precursor fully enters and is adsorbed in the photoresist film body. After the residual metal precursor is removed, an inert gas is introduced for purging. After the purging is completed, deionized water is introduced for infiltration, so that metal nanoparticles are generated inside the photoresist. Finally, after the residual deionized water is removed, an inert gas is introduced for purging, and the above-mentioned gas phase infiltration step is repeated.
[0043] In a specific embodiment of the present invention, the deposition equipment is an atomic layer deposition equipment, model Vecco FijiG2.
[0044] In the hybrid photoresist vapor infiltration in-situ synthesis method provided by the present invention, the photoresist is a light-sensitive material commonly used in microelectronics and semiconductor manufacturing, and can accurately transfer the pattern to a substrate (such as a silicon wafer) by ultraviolet exposure, development and etching. Photoresists are divided into positive photoresists and negative photoresists:
[0045] Positive photoresist: Areas exposed to light (usually UV light) become soluble in a developer and are removed, leaving the unexposed areas.
[0046] Negative photoresist: After exposure to light, the areas will crosslink and become insoluble in the developer, remaining on the substrate, while the unexposed areas will be removed.
[0047] The photoresist is usually composed of a photosensitive resin, a photosensitizer, an organic solvent and additives. After the photoresist undergoes preheating and baking or exposure and development steps, some components disappear through chemical reactions, and the main remaining component is the photosensitive resin, which undergoes cross-linking or structural changes in the above steps to form a stable pattern.
[0048] Among them, the photosensitive resin can be selected from one or more of phenolic resin, acrylic resin or polyamide resin; the photosensitizer can be selected from one or more of triaryl antimony salt, benzophenone or two-photon absorption material; the organic solvent can be selected from one or more of ethyl acetate, acetone or xylene; the additive can be selected from one or more of surfactant (such as polyoxyethylene ether or polyethylene glycol), preservative (such as hydroquinone or sodium benzoate) or antioxidant (such as diphenyl sulfide).
[0049] In a specific embodiment of the present invention, the photoresist is a positive photoresist, the main active ingredient of which is an acrylate copolymer. The product is purchased from Xuzhou Bokang, and the specific model is HTK1062 (248nm) photoresist.
[0050] In a specific embodiment of the present invention, the silicon substrate loaded with photoresist is subjected to ultraviolet exposure and development to obtain a silicon substrate with patterned photoresist. The specific steps of exposure and development are as follows: ultraviolet rays (UV) or electron beams (E-beam) are irradiated onto the photoresist through a mask (usually a transparent glass or quartz plate coated with an opaque photoresist pattern) so that a photochemical reaction occurs in the irradiated photoresist area. Then, a developer is used to develop the exposed photoresist so that the photoresist in the exposed (positive photoresist) or unexposed (negative photoresist) area is dissolved and removed, forming a photoresist structure corresponding to the mask pattern.
[0051] In a specific embodiment of the present invention, the silicon substrate with patterned photoresist is a photoresist on a silicon substrate transformed into a photoresist with spaced line patterns. The spacing of the line patterns is 150-250nm, optionally 150-200nm or 200-250nm, preferably 200nm.
[0052] In the vapor infiltration in-situ synthesis method of the hybrid photoresist provided by the present invention, the thickness of the photoresist loaded on the silicon substrate is 200-400nm, and can be optionally 200-300nm or 300-400nm.
[0053] In the vapor infiltration in-situ synthesis method of hybrid photoresist provided by the present invention, the preheating temperature is 90-120°C, which can be 90-100°C, 100-110°C or 110-120°C, and is preferably 100°C; the preheating time is 25-35min, which can be 25-30min or 30-35min, and is preferably 30min.
[0054] In the in-situ synthesis method of hybrid photoresist by vapor infiltration provided by the present invention, the metal precursor is trimethylaluminum or diethylzinc, preferably trimethylaluminum. In a specific embodiment of the present invention, in the vapor infiltration process, trimethylaluminum or diethylzinc is heated and vaporized in advance, and then introduced into the cavity of the deposition equipment to infiltrate into the photoresist in the form of vapor.
[0055] In the hybrid photoresist vapor infiltration in-situ synthesis method provided by the present invention, the silicon substrate loaded with photoresist and pattern is immersed in the metal precursor atmosphere for infiltration for a time of 15-30 minutes, which can be 15-20 minutes, 20-25 minutes, 25-30 minutes, 20-30 minutes, etc., preferably 20 minutes. Since in the actual operation process of vapor phase cyclic infiltration, the photoresist-covered area on the silicon substrate is vapor-infiltrated with metal oxide, and the exposed area (no photoresist-covered area) on the silicon substrate after exposure and development undergoes metal oxide deposition, so if the single-cycle infiltration time is too short, the metal oxide content in the hybrid photoresist will be low, thereby affecting its etching resistance; and if the time is too long, the metal oxide deposition thickness of the metal oxide deposited in the no photoresist-covered area will be too large, resulting in a decrease in the etching selectivity.
[0056] In the hybrid photoresist vapor infiltration in-situ synthesis method provided by the present invention, the inert gas is argon. In a specific embodiment of the present invention, the purge time of the inert gas is 8-15 minutes, which can be 8-10 minutes, 10-12 minutes, 12-15 minutes or 10-15 minutes, preferably 10 minutes.
[0057] In the in-situ synthesis method of the hybrid photoresist provided by the present invention, the number of cycles of the gas phase infiltration is 1-7, which can be selected as 1-3, 3-5, 5-7, 1-5 or 3-7, preferably 5, and each cycle includes sequentially introducing a metal precursor, an inert gas, deionized water and an inert gas. By changing the number of cycles of the gas phase infiltration cycle, the content of metal nanoparticles generated inside the photoresist can be controlled. A small number of gas phase infiltration cycles will result in a low content of metal oxides in the photoresist film, thereby affecting the etching resistance; after the number of cycles exceeds 5, the content of metal oxides in the bulk phase of the photoresist film reaches saturation, and when the number of cycles continues to increase, the metal oxides tend to be deposited on the surface of the photoresist, causing the etching selectivity to decrease.
[0058] In the hybrid photoresist vapor infiltration in-situ synthesis method provided by the present invention, the molar ratio of the metal precursor and deionized water introduced in each gas infiltration cycle is 1: (1-2), which can be 1: (1-1.5) or 1: (1.5-2), preferably 1: 1 or 1: 2. In a specific embodiment of the present invention, the amount of reactants added is ensured by controlling the single metal precursor ejection pressure in the reaction chamber, the pressure ratio between the inert gas and the deionized water, and the repeatability of the experiment.
[0059] In a specific embodiment of the present invention, the chemical reaction mechanism of generating metal nanoparticles inside the photoresist is as follows: metal precursor trimethylaluminum or diethylzinc diffuses into the photoresist in the form of gas phase. Trimethylaluminum or diethylzinc reacts chemically with polar groups in the photoresist. After deionized water is introduced, trimethylaluminum or diethylzinc further reacts with water to remove all ligands and form aluminum oxide or zinc oxide nanoparticles inside the photoresist.
[0060] In the hybrid photoresist vapor infiltration in-situ synthesis method provided by the present invention, the metal nanoparticles are aluminum oxide or zinc oxide, and the mass fraction of the metal nanoparticles in the hybrid photoresist is 2-10wt%, which can be 2-4wt%, 4-6wt%, 6-8wt% or 8-10wt%. If the content of metal oxide nanoparticles in the hybrid photoresist is less than 2wt%, the improvement of etching resistance will be insignificant or no improvement.
[0061]
Hybrid photoresist
[0062] The second aspect of the present invention provides a hybrid photoresist prepared by the synthesis method as described above.
[0063] The present invention measures the relative etching resistance of the target material (silicon substrate) and the mask material (photoresist) under the same etching conditions by etching selectivity. Etching selectivity = etching rate of target material (silicon substrate) / etching rate of mask material (photoresist). Wherein, the etching rate refers to the rate at which the material is removed during the etching process. In a specific embodiment of the present invention, the rate of change of the thickness of the photoresist (or silicon substrate) is used to represent it, that is, etching rate = change of thickness of the photoresist (or silicon substrate) / time.
[0064] In a specific embodiment of the present invention, due to the presence of a metal oxide film on the silicon surface after the vapor infiltration treatment, the formula of the etching selectivity is modified to: the etching rate of the target material (silicon substrate with a metal oxide film deposited thereon) divided by the etching rate of the mask material (hybrid photoresist), that is, the etching selectivity = the etching rate of the silicon substrate with a metal oxide film deposited thereon / the etching rate of the hybrid photoresist of the present invention. In a specific embodiment of the present invention, the etching selectivity increases, and the etching selectivity reaches 50 when the number of vapor infiltration turns is 5 turns. The high etching selectivity indicates that the hybrid photoresist of the present invention has excellent etching resistance.
[0065]
application
[0066] The present invention also provides the use of the hybrid photoresist prepared by the synthesis method described above in etching.
[0067]
Etching method
[0068] The present invention also provides an etching method, which comprises the following steps:
[0069] The silicon substrate loaded with hybrid photoresist is etched once to achieve pattern transfer to the silicon substrate, and then the hybrid photoresist remaining on the surface of the silicon substrate is removed by secondary etching; wherein the hybrid photoresist is the hybrid photoresist prepared by the above-mentioned synthesis method.
[0070] Specifically: a silicon substrate loaded with hybrid photoresist is placed in the cavity of a reactive ion etching device, and a first etching is performed to achieve the transfer of the pattern to the silicon substrate, and then the sample is placed in the cavity of the reactive ion etching device again, and a second etching is performed to remove the photoresist remaining on the surface of the silicon substrate. The specific process of transferring the pattern to the silicon substrate is that the silicon substrate loaded with photoresist is exposed to ultraviolet light and developed to obtain a silicon substrate with patterned photoresist, and then the pattern is further transferred to the silicon substrate by a first etching.
[0071] In the etching method provided by the present invention, the etching gas for the primary etching is a mixture of sulfur hexafluoride and oxygen, and the flow ratio of sulfur hexafluoride to oxygen is (9-11):1, which can be optionally (9-10):1 or (10-11):1, and is preferably 10:1.
[0072] In a specific embodiment of the present invention, the specific process of the single etching is to continuously introduce a mixture of sulfur hexafluoride and oxygen into the cavity of the reactive ion etching equipment so that the pressure in the cavity is stabilized at 90-110 mTorr, which can be selected as 90-100 mTorr or 100-110 mTorr, and preferably 100 mTorr. After the pressure stabilization time reaches 25-35s, which can be selected as 25-30s or 30-35s, and preferably 30s, 200-300 watts, 200-250 watts or 250-300 watts, and preferably 250 watts of radio frequency power are applied, and etching is performed for 20-40s, which can be selected as 20-30s or 30-40s, and preferably 30s.
[0073] In the etching method provided by the present invention, the etching gas for the secondary etching is oxygen, and the gas flow rate is 35-45 mTorr, which can be selected as 35-40 mTorr or 40-45 mTorr, and is preferably 40 mTorr.
[0074] In the etching method provided by the present invention, the specific process of the secondary etching is to continuously introduce oxygen into the cavity of the reactive ion etching device and stabilize the pressure in the cavity at 15-25 mTorr, which can be 15-20 mTorr or 20-25 mTorr, preferably 20 mTorr, and after the pressure stabilization time reaches 25-35s, which can be 25-30s or 30-35s, preferably 30s, apply 200-300 watts, which can be 200-250 watts or 250-300 watts, preferably 250 watts of radio frequency power, and perform etching for 4-6 minutes, which can be 4-5 minutes or 5-6 minutes, preferably 4 minutes. If the oxygen plasma etching time is insufficient, photoresist residue will be caused.
[0075] In order to make the technical means, creative features, objectives and effects achieved by the present invention easier to understand, the present invention is described in detail below in conjunction with embodiments and drawings.
[0076] In the following examples, unless otherwise specified, all reaction raw materials are commercially available products.
[0077] Unless otherwise specified, the purity of each product in each embodiment of the present invention exceeds 98%.
[0078] Example 1
[0079] (1) Preparation of silicon substrate with patterned photoresist:
[0080] A 300-nanometer-thick photoresist is prepared on a cleaned silicon substrate by spin coating; the photoresist on the silicon substrate is transformed into a photoresist with a line pattern with a width of 200 nanometers by ultraviolet exposure and development.
[0081] (2) In-situ synthesis of hybrid photoresist (doped aluminum oxide) by vapor infiltration method:
[0082] After the silicon substrate with patterned photoresist is placed in the chamber of an atomic layer deposition device at 100°C and preheated for half an hour, the connection between the chamber and the pump is cut off, and trimethylaluminum with a pressure of about 1.5 torr is introduced and retained in the chamber for 20 minutes, so that the trimethylaluminum fully diffuses into and adsorbs in the photoresist film phase; the connection between the chamber and the pump is restored to remove the residual trimethylaluminum and high-purity argon is introduced for 10 minutes of purging; then deionized water with a pressure of about 2 torr is introduced to produce metal nanoparticles inside the photoresist; finally, the connection between the chamber and the pump is restored to remove the residual deionized water and high-purity argon is introduced for 10 minutes of purging, and after 1-7 cycles of gas phase infiltration, a reinforced hybrid photoresist is obtained. The content of metal nanoparticles in the hybrid photoresist finally obtained is 2wt%-10wt%. As the number of cycles increases, the bulk content increases. In Example 1, the content of metal nanoparticles in the hybrid photoresist after one cycle of vapor phase infiltration treatment is 2.46 wt %; the content of metal nanoparticles in the hybrid photoresist after five cycles of vapor phase infiltration treatment is 7.56 wt %.
[0083] (3) Primary etching (transfer of pattern to silicon substrate):
[0084] A silicon substrate loaded with hybrid photoresist was placed in the chamber of a reactive ion etching device, and a mixed gas of sulfur hexafluoride and oxygen was continuously introduced at a flow rate ratio of 10:1 to stabilize the pressure in the chamber at 100 mTorr. After the pressure was stabilized for 30 seconds, a 250-watt RF power was applied for etching for 30 seconds.
[0085] (4) Secondary etching (removing residual photoresist on the silicon substrate):
[0086] The silicon substrate after pattern transfer was placed in the chamber of a reactive ion etching device, oxygen was continuously introduced and the pressure was stabilized at 20 mTorr. After the pressure was stabilized for 30 seconds, 250 watts of radio frequency power was applied for etching for 5 minutes.
[0087] Example 2
[0088] (1) Preparation of (patternless) photoresist layer silicon substrate:
[0089] A 300-nanometer-thick photoresist is prepared on a cleaned silicon substrate by spin coating; the silicon substrate coated with the photoresist is placed on a heating plate and baked for 10 minutes.
[0090] (2) In-situ synthesis of hybrid photoresist (doped aluminum oxide) by vapor infiltration method:
[0091] The silicon substrate coated with photoresist is placed in a cavity at 100°C for preheating for half an hour, and then trimethylaluminum with a pressure of about 1.5 torr is introduced while the cavity and the pump are cut off and retained in the cavity for 20 minutes, so that trimethylaluminum fully diffuses into and adsorbs in the photoresist film phase; the connection between the cavity and the pump is restored to remove the residual trimethylaluminum and high-purity argon is introduced for 10 minutes of purging; then ionized water with a pressure of about 2 torr is introduced to produce metal nanoparticles inside the photoresist; finally, the connection between the cavity and the pump is restored to remove the residual deionized water and high-purity argon is introduced for 10 minutes of purging, and after 1-7 cycles of gas phase infiltration, a reinforced hybrid photoresist is obtained. The content of metal nanoparticles in the hybrid photoresist finally obtained is 2wt%-10wt%. In Example 2, the content of metal nanoparticles in the hybrid photoresist after 1 cycle of gas phase infiltration treatment is 2.46wt%; the content of metal nanoparticles in the hybrid photoresist after 5 cycles of gas phase infiltration treatment is 7.56wt%.
[0092] (3) Etching of hybrid photoresist (doped aluminum oxide) (the hybrid photoresist itself is etched):
[0093] The sample strengthened by vapor infiltration was placed in the chamber of a reactive ion etching device, and a mixed gas of sulfur hexafluoride and oxygen was continuously introduced at a flow ratio of 10:1 to stabilize the pressure in the chamber at 100 mTorr. After the pressure stabilized for 30 seconds, a 250-watt RF power was applied for etching for 60 seconds.
[0094] Anti-etching performance test:
[0095] The thickness change of the hybrid photoresist (doped aluminum oxide) after etching in step (3) was measured by an ellipsometric light device (JA Woollam RC2 UI) to calculate the etching rate of the hybrid photoresist of Example 2 under different gas phase penetration circles, as shown in FIG. Figure 3 shown.
[0096] Example 3
[0097] (1) Preparation of (patternless) photoresist layer silicon substrate:
[0098] A 300-nanometer-thick photoresist is prepared on a cleaned silicon substrate by spin coating; the silicon substrate coated with the photoresist is placed on a heating plate and baked for 10 minutes.
[0099] (2) In-situ synthesis of hybrid photoresist (doped zinc oxide) by vapor infiltration method:
[0100] The silicon substrate coated with photoresist is placed in a cavity at 100°C for preheating for half an hour, and then diethyl zinc with a pressure of about 1.5 torr is introduced while the cavity and the pump are cut off and kept in the cavity for 20 minutes, so that diethyl zinc fully diffuses into and adsorbs in the photoresist film body; the connection between the cavity and the pump is restored to remove the residual diethyl zinc and high-purity argon is introduced for 10 minutes of purging; then ionized water with a pressure of about 2 torr is introduced to produce metal nanoparticles inside the photoresist; finally, the connection between the cavity and the pump is restored to remove the residual deionized water and high-purity argon is introduced for 10 minutes of purging, and after 1-7 cycles of gas phase infiltration, a reinforced hybrid photoresist is obtained. The content of metal nanoparticles in the hybrid photoresist finally obtained is 5wt%-8wt%. In Example 3, the content of metal nanoparticles in the hybrid photoresist after 1 cycle of gas phase infiltration treatment is 5.69wt%; the content of metal nanoparticles in the hybrid photoresist after 5 cycles of gas phase infiltration treatment is 7.42wt%.
[0101] (3) Etching of hybrid photoresist (doped zinc oxide) (the hybrid photoresist itself is etched):
[0102] The sample strengthened by vapor infiltration was placed in the chamber of a reactive ion etching device, and a mixed gas of sulfur hexafluoride and oxygen was continuously introduced at a flow ratio of 10:1 to stabilize the pressure in the chamber at 100 mTorr. After the pressure stabilized for 30 seconds, a 250-watt RF power was applied for etching for 60 seconds.
[0103] Anti-etching performance test:
[0104] The thickness change of the hybrid photoresist (doped zinc oxide) after etching in step (3) was measured by an ellipsometric light device (JA Woollam RC2 UI) to calculate the etching rate of the hybrid photoresist of Example 3 under different gas phase permeation circles, as shown in FIG. Figure 3 shown.
[0105] Comparative Example 1
[0106] (1) Preparation of silicon substrate with metal oxide (aluminum oxide) film deposited on it:
[0107] A silicon substrate with a polyimide tape on one end is placed in a chamber at 100°C for preheating for half an hour, and then the chemical precursor trimethylaluminum is introduced at a pressure of about 1.5 torr while the chamber and the pump are cut off and kept in the chamber for 20 minutes; the connection between the chamber and the pump is restored to pump out the residual trimethylaluminum and high-purity argon is introduced for 10 minutes of purge; then, deionized water is introduced as a chemical precursor at a pressure of about 2 torr; finally, the connection between the chamber and the pump is restored to pump out the residual deionized water and high-purity argon is introduced for 10 minutes of purge, and after 1-7 cycles of deposition, a silicon substrate deposited with a metal oxide (aluminum oxide) film is obtained.
[0108] (2) Etching of silicon substrates deposited with metal oxide (aluminum oxide) films:
[0109] A silicon substrate deposited with a metal oxide (aluminum oxide) film is placed in the chamber of a reactive ion etching device, and a mixed gas of sulfur hexafluoride and oxygen is continuously introduced at a flow ratio of 10:1 to stabilize the pressure in the chamber at 100 mTorr. After the pressure stabilizes for 30 seconds, a 250-watt RF power is applied for etching for 60 seconds.
[0110] Anti-etching performance test:
[0111] The thickness change of the silicon substrate with the metal oxide (aluminum oxide) film deposited thereon in Comparative Example 1 after etching was measured by a step profiler (Bruker Dektak XT) to calculate the etching rate of the silicon substrate with the metal oxide (aluminum oxide) film deposited thereon under different gas phase penetration cycles, as shown in FIG. Figure 4 shown.
[0112] Comparative Example 2
[0113] (1) Preparation of silicon substrate with metal oxide (zinc oxide) thin film deposited on it:
[0114] A silicon substrate with a polyimide tape attached to one end is placed in a chamber at 100°C for preheating for half an hour, and then the chemical precursor diethyl zinc at a pressure of about 1.5 torr is introduced while the chamber and the pump are cut off and retained in the chamber for 20 minutes; the connection between the chamber and the pump is restored to pump out the residual diethyl zinc and high-purity argon is introduced for 10 minutes of purging; then, deionized water as a chemical precursor at a pressure of about 2 torr is introduced; finally, the connection between the chamber and the pump is restored to pump out the residual deionized water and high-purity argon is introduced for 10 minutes of purging, and after 1-7 cycles of deposition, a silicon substrate deposited with a metal oxide (zinc oxide) film is obtained.
[0115] (2) Etching of silicon substrates deposited with metal oxide (zinc oxide) films:
[0116] A silicon substrate deposited with a metal oxide (zinc oxide) film was placed in the chamber of a reactive ion etching device, and a mixed gas of sulfur hexafluoride and oxygen was continuously introduced at a flow ratio of 10:1 to stabilize the pressure in the chamber at 100 mTorr. After the pressure stabilized for 30 seconds, a 250-watt RF power was applied for etching for 60 seconds.
[0117] Anti-etching performance test:
[0118] The thickness change of the silicon substrate with the metal oxide (zinc oxide) film deposited thereon in Comparative Example 2 after etching was measured by a step profiler (Bruker Dektak XT) to calculate the etching rate of the silicon substrate with the metal oxide (zinc oxide) film deposited thereon under different gas phase permeation cycles, as shown in FIG. Figure 4 shown.
[0119] Comparative Example 3
[0120] (1) Preparation of (patternless) photoresist layer silicon substrate:
[0121] A 300-nanometer-thick photoresist is prepared on a cleaned silicon substrate by spin coating; the silicon substrate coated with the photoresist is placed on a heating plate and baked for 10 minutes.
[0122] (2) Pure photoresist etching:
[0123] The sample spin-coated with photoresist was placed in the chamber of a reactive ion etching device, and a mixed gas of sulfur hexafluoride and oxygen was continuously introduced at a flow ratio of 10:1 to stabilize the pressure in the chamber at 100 mTorr. After the pressure stabilized for 30 seconds, a 250-watt RF power was applied for etching for 60 seconds.
[0124] Anti-etching performance test:
[0125] The thickness change of the pure photoresist (without doping components) after etching in Comparative Example 3 was measured by an elliptically polarized light device (JA Woollam RC2 UI) to calculate the etching rate of the pure polymer-based photoresist, as shown in FIG. Figure 5 shown.
[0126] Combining Examples 2-3 and Comparative Examples 1-3, the etching selectivity is equal to the target material etching rate (silicon substrate with metal oxide film deposited) divided by the mask material etching rate (hybrid photoresist). That is, the etching selectivity (doped aluminum oxide) = the etching rate of Comparative Example 1 / the etching rate of Example 2; the etching selectivity (doped zinc oxide) = the etching rate of Comparative Example 2 / the etching rate of Example 3. The obtained etching selectivity is Figure 5 The performance of pure photoresist is shown in Figure 5 The value represented by the horizontal line is the etching selectivity of 0 gas phase infiltration treatment. As the number of gas phase infiltration cycles increases, the etching selectivity increases, and both etching selectivities increase, and when the number of gas phase infiltration cycles is 5 cycles, the etching selectivity reaches a maximum value of 50, indicating that the hybrid photoresist of the present invention has a more excellent etching resistance than the traditional pure polymer-based photoresist.
[0127] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A hybrid photoresist vapor infiltration in-situ synthesis method, characterized in that: The steps include: The silicon substrate loaded with photoresist is placed in a deposition device for preheating, and then a metal precursor, an inert gas, deionized water and an inert gas are introduced in sequence for gas phase infiltration circulation to generate metal nanoparticles inside the photoresist to obtain a hybrid photoresist.
2. The hybrid photoresist vapor infiltration in-situ synthesis method according to claim 1, characterized in that: The photoresist is composed of photosensitive resin, photosensitizer, organic solvent and additives.
3. The vapor infiltration in-situ synthesis method of hybrid photoresist according to claim 1, characterized in that: Includes any of the following features: A1) exposing the silicon substrate loaded with the photoresist to ultraviolet light and developing the substrate to obtain a silicon substrate with a patterned photoresist; A2) the thickness of the photoresist loaded on the silicon substrate is 200-400nm; A3) the preheating temperature is 90-120°C; A4) The preheating time is 25-35min; A5) the metal precursor is trimethylaluminum or diethylzinc; A6) the inert gas is argon; A7) the number of cycles of the vapor phase infiltration is 1-7; each cycle includes sequentially introducing a metal precursor, an inert gas, deionized water and an inert gas; A8) The molar ratio of the metal precursor to deionized water introduced in each gas phase infiltration cycle is 1:(1-2).
4. The method for in-situ synthesis of hybrid photoresist by vapor infiltration according to claim 1, characterized in that: Includes any of the following features: A9) the metal nanoparticles are aluminum oxide or zinc oxide; A10) The mass fraction of the metal nanoparticles in the hybrid photoresist is 2-10 wt %.
5. The vapor infiltration in-situ synthesis method of hybrid photoresist according to claim 3, characterized in that: The silicon substrate with patterned photoresist is a photoresist on a silicon substrate transformed into a photoresist with spaced line patterns.
6. A hybrid photoresist prepared by the synthesis method according to any one of claims 1 to 5.
7. Use of the hybrid photoresist as claimed in claim 6 in etching.
8. An etching method, characterized in that: The etching method comprises the following steps: etching a silicon substrate loaded with a hybrid photoresist once to achieve pattern transfer to the silicon substrate, and then performing a secondary etching to remove the hybrid photoresist remaining on the surface of the silicon substrate; Wherein, the hybrid photoresist is the hybrid photoresist as claimed in claim 6.
9. The etching method according to claim 8, characterized in that: Also includes any one or more of the following features: B1) The primary etching and / or secondary etching is performed in a reactive ion etching device; B2) The etching gas for the primary etching is a mixture of sulfur hexafluoride and oxygen; B3) The time of one etching is 20-40s; B4) The etching gas for the secondary etching is oxygen; B5) The secondary etching time is 4-6 minutes.
10. The etching method according to claim 9, characterized in that: The flow ratio of sulfur hexafluoride and oxygen described in feature B2) is (9-11):1.
Citation Information
Patent Citations
Inorganic-Infiltrated Polymer Hybrid Thin Film Resists for Advanced Lithography
US20200285148A1